HUBUNGAN ANTARA KEBIASAAN MEMBACA DAN KEMAMPUAN MENULIS NARASI SISWA KELAS IX SMP - Pudan Doli Situmorang; Siti Samhati; Eka Sofia Agustina (FKIP Universitas Lampung, 2013)
Lack of skills and abilities of students in writing a good and correct essay due to more frequent use of verbal language and more likely to use non formal language.The research problem is: